Oil Production and Groundwater Quality in the Edwards-Trinity Plateau Aquifer, Texas - Paul F. Hudak (The Scientific World Journal)
Chloride concentrations and chloride/bromide ratios from 198 water wells in the Edwards-Trinity Plateau Aquifer were compiled, mapped, and evaluated within the context of regional geology and land use. The study area occupies eight counties in west-central Texas, within which oil production and agriculture are predominant land uses. Samples from 49 wells had chloride concentrations above the 250 mg/l secondary drinking water standard, 22 samples had greater than 500 mg/l chloride, and 9 samples exceeded 1000 mg/l chloride. Of the 22 samples above 500 mg/l chloride, 10 had relatively low chloride/bromide ratios of less than 300, consistent with oilfield brine, and 2 had ratios above 2000, consistent with groundwater impacted by evaporite dissolution. The remaining ten samples had chloride/bromide ratios ranging from 300 to 2000, consistent with partial mixing of unimpaired groundwater with evaporite-laden water. There were no significant correlations between chloride concentration and well depth, inconsistent with contaminants originating at the land surface. Results of this study suggest that evaporite dissolution and oilfield brine locally impact the Edwards-Trinity Plateau Aquifer, but the problem is not regionally pervasive.